DAMPAK PBL BERMUATAN TUTOR SEBAYA TERHADAP PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH SISWA SMP - Apolonia Hendrice Ramda; Melania Delima; Fransiskus Nendi (Jurnal Pendidikan dan Kebudayaan Missio, 2022)
Mathematical problem solving ability is an ability that must be possessed by students. Therefore, every student must have this ability. One way to improve mathematical problem solving skills is to use the Problem Base Learning model with peer tutors. This study aims to determine the improvement of students' mathematical problem solving abilities using the Problem Based Learning (PBL) model with peer tutors compared to the improvement of students' mathematical problem solving abilities using conventional learning models. This research is a quasi-experimental research. The population in this study was class VIII of SMP Negeri 11 Ruteng for the Academic Year 2021/2022 which was divided into five classes. Before determining the experimental and control classes, a class equivalence test was first carried out and the five equivalent classes were obtained. Two classes were randomly selected to be the experimental class and the control class from all five classes using the class equivalence test. Both classes received pretest and posttest by working on mathematical problem-solving ability test questions that had been tested for validity and reliability before. From the data obtained, the hypothesis t test was then carried out. The results of the hypothesis test showed that it was rejected and accepted. Based on the results of the t test on the gain score data using the independent sample t test, the value obtained is > , and the average gain in the experimental class is 0.63 which is higher than the average gain in the control class, which is 0.45. The results of this study indicate that the increase in mathematical problem solving abilities of students who use the Problem Based Learning (PBL) model with Peer Tutors is higher than that of students who take conventional learning. Based on the results of this study, teachers can use the Problem Based Learning model of peer tutoring to improve the mathematical problem solving abilities of junior high school students